Інформаційно-технологічна підтримка процедури вибору та контролю показників діяльності торгівельного підприємства - Орловський, Дмитро Леонідович; Пилипець, М. С. (НТУ "ХПІ", 2013)
This article addresses the information technology support for choice, accounting and control of multiple indicators of commercial enterprises within the overall strategy of customer relationship management, in particular the question of forming complex pathways by which the indicator values are controlled and predicted.
Keywords: взаімовідносини; клієнти; система показників; показники ефективності; забезпечення програмне; прогнозування